OC fault diagnosis of multilevel inverter using SVM technique and detection algorithm. (December 2021) - Sarita, Kumari; Kumar, Sachin; Saket, R.K.
Abstract: The Open Circuit (OC) faults occurring in switches of Multilevel Converters (MLC) may lead to undesirable operation of the converter. Therefore, fault detection and its localization in minimum time are necessary. This paper focuses on the fast fault detection algorithm based on the two samples technique and the fault localization algorithm using the Entropy of Wavelet Packets (EWP) as a feature. The EWP feature is used to classify and localize the OC faults in Insulated Gate Bipolar Transistors (IGBTs) of three-phase, three-level inverter using Support Vector Machine (SVM) based fault classification algorithm. The proposed technique can detect the fault in single IGBT and multiple IGBTs in a lesser time range of microseconds to 0.33 ms. It gives better performance and accuracy (99.70%) than previously proposed SVM algorithms, as the EWP-based feature extraction process used in this paper is simple and accurate with a less computational burden. Graphical abstract: Highlights: An observer-based algorithm is proposed using two samples-based technique. The Entropy of Wavelet Packets (EWP-SVM) technique is used for fault diagnosis. The proposed algorithm can detect the faults in a single IGBT and multiple IGBTs. The technique is faster and accurate than techniques available in the literature. The comparison of detection time of different techniques is also discussed.